2020
DOI: 10.1002/cre2.309
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of aging, complete tooth loss, and having a dental visit in the last 12 months

Abstract: Objectives: To evaluate the extent to which dental health care visits in the past year differed among older adults with and without edentulism. Material and Methods: We conducted a cross-sectional study using the 2017 Medical Expenditure Panel Survey among participants aged ≥50 years (n = 10,480, weighted = 112,116,641). Two self-reported outcome variables were used: loss of all teeth from upper and lower jaws (yes/no) and dental visit in the last 12 months (yes/no). Logistic models were used to estimate adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Interestingly, individuals reporting higher frequency of dental care over the follow‐up time had higher incidence of tooth loss than those not visiting the dentist in the same period. It would be expected that visiting a dentist would prevent tooth loss (Foiles Sifuentes et al 2020; Li et al 2011). However, other studies have shown associations similar to that of the present study (Bhat et al 2018; Gilbert et al 2003), which may be explained in part by social disparities, reasons to consult a dentist and by the fact that the majority of tooth extractions are performed in dental offices/services.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, individuals reporting higher frequency of dental care over the follow‐up time had higher incidence of tooth loss than those not visiting the dentist in the same period. It would be expected that visiting a dentist would prevent tooth loss (Foiles Sifuentes et al 2020; Li et al 2011). However, other studies have shown associations similar to that of the present study (Bhat et al 2018; Gilbert et al 2003), which may be explained in part by social disparities, reasons to consult a dentist and by the fact that the majority of tooth extractions are performed in dental offices/services.…”
Section: Discussionmentioning
confidence: 99%
“…However, the aging process itself is also not the main predic- previous study showed an association between advanced age and edentulism. 50 Relative to the subgroup aged 50-59 years, older adults aged 60-69 years presented 1.65 the odds of edentulism, while the older subgroup aged ≥80 years presented 5.84 the odds of edentulism. 50 Interestingly, individuals without edentulism showed an increase in the prevalence of oral health care visits with aging, when the opposite occurred to the group with edentulism.…”
Section: Tooth Lossmentioning
confidence: 94%
“…50 Relative to the subgroup aged 50-59 years, older adults aged 60-69 years presented 1.65 the odds of edentulism, while the older subgroup aged ≥80 years presented 5.84 the odds of edentulism. 50 Interestingly, individuals without edentulism showed an increase in the prevalence of oral health care visits with aging, when the opposite occurred to the group with edentulism. 50 This finding reinforces the importance of regular visits to an oral health care provider during the aging process.…”
Section: Tooth Lossmentioning
confidence: 94%
“…Complete tooth loss (edentulism) is also associated with a host of noncommunicable diseases, including malnutrition, obesity, cardiovascular diseases, diabetes, respiratory diseases, and cancers (Emami et al 2013;Felton 2016) Sifuentes et al 2020). Dental care is important even with a lack of natural teeth to maintain the fit of dentures and monitor health changes in the mouth (e.g., oral cancer).…”
Section: Introductionmentioning
confidence: 99%